Politeness in the Toba Batak Ethnic Panaekkon Saring-Saring Ceremony: Normative Study - Murni Simarmata; Flansius Tampubolon; Yustina Jindi Lusmiran Simamora; Hod Burju Pakpahan; Dion Nardi Pangaribuan (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
The Panaekkon Saring-saring ceremony in the Toba Batak community is part of a diverse and unique set of traditional ceremonies. This study aims to uncover and explore in detail the values of politeness embodied in the Panaekkon Sapada ceremony performed by the Toba Batak community, using a normative study approach. The Panaekkon Saring-saring ceremony is a ritual for moving and re-placing the bones of saur matua, revered ancestors. This study employed a literature review method, examining various literature, including books, scientific articles, and previous research related to norms of politeness, traditional communication, and social ethics in the Toba Batak community. The normative approach was used to examine how traditional values serve as the basis for expected behavior in social interactions and traditional communication that occur during the ceremony. The results show that politeness and courtesy in the Panaekkon Saring-saring ceremony have profound meaning, reflected not only in speech but also in attitudes, actions, and the use of traditional symbols. From a linguistic perspective, politeness is evident in the use of formal, orderly, and respectful traditional language for the structure of family relationships (partuturon). Meanwhile, politeness is also reflected in the solemn attitude of the Tor-tor, as well as the ability to control emotions and maintain respect for the sanctity of ancestral graves. Thus, politeness and courtesy in the Panaekkon Saring-Saring Ceremony are not only elements of cultural aesthetics but also constitute the cultural aesthetic.